In defence of Rebel Angel Theodicy - Forrest, Peter (Religious studies, 2026)
Rebel Angel Theodicy - often called Satan Theodicy - is the thesis that horrendous evils are directly or indirectly caused by angels who disobeyed God. In this article, I defend it, developing Gary Emberger’s suggestion that they influenced the course of evolution. After defending speculative theodicy, I expound Rebel Angel Theodicy and reply to seven objections that explicate the widespread judgement of implausibility:1. That the existence of angels is metaphysically problematic.2. That God has no good reason to create angels.3. That angels have no power to harm human beings.4. That God, foreknowing the possibility of rebellion, would not delegate to angels the power to guide evolution.5. That even if there was a good reason for God to delegate this power to angels it is metaphysically impossible for an omnipotent God to do so.6. That God, knowing of the angels’ rebellion, would subsequently intervene to put evolution back onto the preferred divine plan.7. That there is no plausible motive for angels to rebel.